2018
DOI: 10.1099/jmm.0.000725
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of double-carbapenem combinations against OXA-48-producing Klebsiella pneumoniae isolates using time–kill studies

Abstract: Dual combinations of carbapenems, including those containing sub-inhibitory concentrations of antibiotics, were synergistic against multidrug-resistant (MDR) and extensively drug-resistant (XDR) K. pneumoniae isolates harbouring blaOXA-48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Administration of a double carbapenem (with or without colistin) seems a promising salvage treatment in infections caused by PDR isolates harboring serine-carbapenemases. In vitro data showed synergistic activity of DCC against OXA-48 producing MDR and XDR K. pneumoniae (134). Finally, two kidney transplant recipients were reportedly cured with DCC plus oral fosfomycin from urinary tract infections caused by NDM-harboring Enterobacteriaceae (135).…”
Section: Old and Established Antibioticsmentioning
confidence: 99%
“…Administration of a double carbapenem (with or without colistin) seems a promising salvage treatment in infections caused by PDR isolates harboring serine-carbapenemases. In vitro data showed synergistic activity of DCC against OXA-48 producing MDR and XDR K. pneumoniae (134). Finally, two kidney transplant recipients were reportedly cured with DCC plus oral fosfomycin from urinary tract infections caused by NDM-harboring Enterobacteriaceae (135).…”
Section: Old and Established Antibioticsmentioning
confidence: 99%
“…There have been a number of case reports and series describing treatment failures with carbapenem-containing regimens in the treatment of OXA-48-producing bacterial infections (4,(27)(28)(29). Dual carbapenem combinations, particularly those with imipenem, have shown synergy in vitro against both OXA-48 and KPC producers (30,31). Although, only some study isolates (K. pneumoniae but not recombinant E. coli) showed this result and produced values close to the cutoff value for defining synergy (30).…”
mentioning
confidence: 99%
“…However, an in vitro study [59] has indicated that in DCT, the imipenem-containing combinations show the most efficacy in the treatment for carbapenemase-producing K. pneumoniae infection, while ertapenem may not be the best option to inactivate carbapenemases. This may be related to particularly enhanced in vitro activity of imipenem-containing combinations, even imipenem at sub-inhibitory concentrations [65]. However, in vivo data on imipenem-containing DCT are limited, which may be attributed to the central nervous system toxicity of imipenem and short stability of intravenous preparation [56,66].…”
Section: Discussionmentioning
confidence: 99%